Caffeine consumption during development alters spine density and recovery from repetitive mild traumatic brain injury in young adult rats. Issue 4 (24th November 2019) - Christensen, Jennaya; Yamakawa, Glenn R.; Salberg, Sabrina; Wang, Melinda; Kolb, Bryan; Mychasiuk, Richelle
Abstract: Caffeine is the most commonly used psychostimulant throughout the world, with its consumption being especially prevalent among adolescents and young adults, as over 75% of this group consumes caffeine daily. Similarly, the adolescent and young adult age group exhibit the highest incidence of traumatic brain injury (TBI). Given that both caffeine consumption and mild TBI (mTBI) are more prevalent among the late adolescent/young adult age group and that changes in dendritic spine morphology during this developmental period are poorly understood, this study sought to examine the effects of caffeine consumption during late adolescence/early adulthood on recovery from repetitive mTBI (RmTBI). The study specifically focused on changes to neuronal dendritic morphology as synaptic changes likely underlie long‐term behavioral outcomes. The results demonstrate that during young adulthood caffeine consumption differentially affects the RmTBI outcomes of males and females, where the effects of caffeine and RmTBI were often additive in males while being equally detrimental, but rarely additive, in females. In general, caffeine and RmTBI induced the greatest impairments in males on cognitive and motor tasks whereas in females the most significant detriments were on pain‐related tasks. Both caffeine and RmTBI increased spine density in the Cg3 (medial prefrontal cortex [mPFC]), AID (orbitofrontal cortex [OFC]), and nucleus accumbens (NAc), which is proposed to reflect an impairment in the normal pruning processes. Overall, despite caffeine's neuroprotective abilities among other age groups, this study offers concerning results regarding the detrimental effects of caffeine and RmTBI, in isolation, and especially in combination, in this susceptible population. Abstract : Caffeine consumption during late adolescence has sex‐dependent influences on recovery and synaptic plasticty following repetitive mild traumatic brain injury.